PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MASA PANDEMI COVID 19 DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MI NIHAYATUL AMAL - Rahmat, Ricky; Sutarjo, Sutarjo; Sholeh, Slemat (Universitas Islam Balitar, 2021)
The purpose of this study was to determine student learning outcomes after using the problem based learning model. The population in this study were all students of class VI MI Nihayatul Amal. The sample of this study was in class VI as the experimental class of MI Nihayatul Amal. The method in this study used quantitative methods. The results showed that the application of the problem-based learning model during the Covid-19 pandemic resulted in an increase in the activities and learning outcomes of MI Nihayatul Amal students. The effectiveness of the problem based learning model can improve the results of MI Nihayatul Amal. Problem based learning (PBL) in learning at MI Nihayatul Amal prioritizes student learning styles so that students' potential can be summarized through the inquiry process and accelerate learning to be effective and efficient. One of the appropriate learning methods is to apply the basic problem learning method in simulation and communication learning.